2019
DOI: 10.1186/s12978-018-0661-x
|View full text |Cite
|
Sign up to set email alerts
|

“Our girls need to see a path to the future” --perspectives on sexual and reproductive health information among adolescent girls, guardians, and initiation counselors in Mulanje district, Malawi

Abstract: BackgroundMalawi has one of the highest adolescent pregnancy rates worldwide; at 141 births/1000 girls it is 3-fold higher than the global average. Adolescent pregnancy contributes to poor maternal and neonatal outcomes, school dropout, and poverty. In preparation for an information, education, and communication (IEC) intervention to reduce unintended pregnancy among adolescent girls, formative research was conducted to understand how and what sexual and reproductive health (SRH) information is shared with gir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 33 publications
6
68
0
2
Order By: Relevance
“…This is in agreement with what our study has found as there were mixed feelings among the community leaders about advising adolescents on SRH issues. This has also been reported in another study done in Mulanje, whereby, many of initiation counsellors claimed not to encourage girls to practice sex intercourse but at the same time they reported knowing others who do that [17]. Therefore, our study ascertain the claims made by other studies on adolescents when it comes to addressing SRH and HIV issues.…”
Section: Discussionsupporting
confidence: 74%
“…This is in agreement with what our study has found as there were mixed feelings among the community leaders about advising adolescents on SRH issues. This has also been reported in another study done in Mulanje, whereby, many of initiation counsellors claimed not to encourage girls to practice sex intercourse but at the same time they reported knowing others who do that [17]. Therefore, our study ascertain the claims made by other studies on adolescents when it comes to addressing SRH and HIV issues.…”
Section: Discussionsupporting
confidence: 74%
“…Although many youth indicated that the age of the HSA makes no difference to them, some study participants mentioned that young people prefer to be assisted by younger health workers. Research shows that young people like to discuss issues around sexual and reproductive health with peers or young role models [31,32], but young CBDAs seemed to be scarce in the three study areas. Further research should explore collaboration between HSAs and this voluntary cadre in providing youth-friendly services.…”
Section: Discussionmentioning
confidence: 96%
“…Young people's and adults' notions about adulthood were related to readiness for sex and relationships. The transition from child to adulthood was supported by initiation ceremonies (Nash et al 2019;Frederico, Arnaldo, and Ma ungue 2017). Some young people reported that curiosity or desire made them start sex and relationships.…”
Section: Discussionmentioning
confidence: 99%